Pendidikan Agama Islam Berbasis Kearifan Lokal dalam Pembentukan Karakter Anak Usia Dini di Taman Kanak-Kanak Negeri Alam Kota Singkawang - Walhadi, Walhadi; Putra, Purniadi; Neli, Neli (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
Demoralization and moral decadence in early childhood highlight the importance of values-based character education in the learning system. This study aims to analyze the effectiveness of the integration of local wisdom by Islamic Education teachers in shaping the character of children at the Alam Kota Singkawang State Kindergarten. The method used is qualitative field research employing observation, interviews, and documentation techniques with school principals, teachers, parents, and students. The results indicate that extracurricular activities such as songs, traditional dances with Islamic themes, and the use of Malay traditional attire effectively instill religious, independent, tolerant, disciplined, and responsible character traits in children. In conclusion, this approach is effective in strengthening students' moral identity through the internalization of locally rooted values contextualized within an Islamic framework